Asuhan Kebidanan Ibu Hamil dengan Abortus Imminens Di Rumah Sakit Amelia Kabupaten Kediri - Lina Ratnawati; Winda Ayu Setiyorini (Jurnal Kebidanan Manna, 2023)
Imminent abortion is a pregnancy complication that is often encountered and causes serious emotional burdens, occurs in one in five cases, and increases the risk of miscarriage or incomplete abortion.  The purpose of this study was to provide midwifery care to mothers with Abortion Imminent at Amelia Hospital, Kediri Regency. The method used is a case study.  The sample in this study is a single unit, namely Ny "E" G2P1001 with an indication of abortion imminent   The research was conducted at Amelia Hospital, Pare  15 to 22 June 2022. The data collected in this study was obtained by interview, physical examination, observation, and patient medical records. The results of the assessment on Mrs. "E" were carried out by anamnesis and physical examination which indicated that Mrs. "E" had an imminent abortion.  The care is given by the doctor's advice, namely bed rest, meeting nutritional needs, and observing the mother's condition.  After being treated at the hospital for 5 days, the mother's condition has improved, but there is still a little bleeding and she is allowed to go home, by staying on bed rest, taking medication from the doctor, and avoiding strenuous activities.  After 2 days the mother returned to the hospital with complaints of bleeding in the form of tissue/blood clots, and an ultrasound examination was carried out with the result that there was tissue discharge.  The care provided evaluated the bleeding and a pro curettage was performed on June 22 at 14:00 WIB, at 16:00 WIB a curettage was performed and it was stated that all the products of conception had been removed. The imminent abortion that occurred in Mrs. "E" could not be maintained even though the appropriate care had been given and it became an incomplete abortion that required curettage.  In the case of imminent abortion, it is necessary to comply with total bed rest, take medication, reduce strenuous activity, and comply with the doctor's advice.